Can Amlodipine Improve the Pre-ovulatory Follicle Blood Flow in Women with Polycystic Ovarian Syndrome? - DE Faham; Kh Ali; AE El Din; M Bibars; O Azmy (JRI, 2019)
Background: A reduction in intra-ovarian vascular resistance is necessary to achieve pregnancy in a natural cycle. The aim of this RCT was to detect whether a vasodilator calcium channel blocker, amlodipine, could increase the pre-ovulatory follicular blood flow, enhance follicular maturation in women with PCOS and improve ovulatory outcome.  Methods: Sixty women received induction by clomiphene citrate (CC); thirty were given amlodipine (Amlodipine group) and the other 30 women were given placebo (Placebo group). The pattern of pre-ovulatory follicle blood flow was studied by color and power Doppler ultrasonography pre and post drug administration. Independent t-test was used to compare mean values of the 2 groups. The p<0.05 is considered statistically significant. Results: When comparing the Doppler effect of amlodipine versus placebo in the treatment cycle, it was found that mean value of ovarian arteries (OA) pulsatility index was lower in amlodipine group but it didn't reach statistical significance (p=0.063); however, the mean value of OA resistance index reached statistical significance (p=0.028) in amlodipine group. Moreover, in the second cycle, endometrial thickness was significantly higher (p=0.006) in women of the amlodipine group when compared to those of the placebo group. At least one sonographically detectable mature follicle (≥18 mm) was observed in 54.5% (36/66) during the first cycle. At the second cycle, this proportion significantly rose to 86.7% (26/30) in the amlodipine group, but marginally and non-significantly to 56.7% (17/30) in the placebo group.  Conclusion: Amlodipine as calcium channel blocker was proved to have a role in improving ovarian blood flow at the time of ovulation and enhancing follicular maturation and thus, it may increase the chances of conception.